A Personalized 14-3-3 Disease-Targeting Workflow Yields Repositioning Drug Candidates - Yonika A. Larasati; Gonzalo P. Solis; Alexey Koval; Christian Korff; Vladimir L. Katanaev (Cells)
Rare diseases typically evade the application of the standard drug discovery and development pipelines due to their understudied molecular etiology and the small market size. Herein, we report a rare disease-directed workflow that rapidly studies the molecular features of the disorder, establishes a high-throughput screening (HTS) platform, and conducts an HTS of thousands of approved drugs to identify and validate repositioning drug candidates. This study examines the pediatric neurological disorder caused by de novo mutations in YWHAG, the gene encoding the scaffolding protein 14-3-3γ, and the workflow discovers nuclear relocalization and a severe drop in 14-3-3γ binding to its phosphorylated protein partners as the key molecular features of the pathogenic hotspot YWHAG mutations. We further established a robust in vitro HTS platform and screened ca. 3000 approved drugs to identify the repositioning drug candidates that restore the deficient 14-3-3γ-phosphotarget interactions. Our workflow can be applied to other 14-3-3-related disorders and upscaled for many other rare diseases.